2018
DOI: 10.1016/j.biopha.2018.07.147
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine: A prospective natural lead for anticancer drug discovery

Abstract: Nature is the most abundant source for novel drug discovery. Lycorine is a natural alkaloid with immense therapeutic potential. Lycorine is active in a very low concentration and with high specificity against a number of cancers both in vivo and in vitro and against various drug-resistant cancer cells. This review summarized the therapeutic effect and the anticancer mechanisms of lycorine. At the same time, we have discussed the pharmacology and comparative structure-activity relationship for the anticancer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 144 publications
(176 reference statements)
3
63
0
3
Order By: Relevance
“…Based on the experience gained during the SARS epidemic, we selected plants that are effective before or at the initial stage of infection. Roy et al suggested a number of medicinal plants with these properties, although most of them grow in warm and hot areas, but there are plants found in Northeast Asia [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the experience gained during the SARS epidemic, we selected plants that are effective before or at the initial stage of infection. Roy et al suggested a number of medicinal plants with these properties, although most of them grow in warm and hot areas, but there are plants found in Northeast Asia [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…( Amaryllidaceae ) originally grew in China, Korea and Nepal and was later distributed to other countries, including Russia. It is a source of pharmacologically active alkaloids, with lycorine being the main one [ 11 , 23 , 24 , 25 , 26 ]. Lycorine has selective antiviral activity, including against severe acute respiratory syndrome associated with coronavirus and influenza virus [ 11 , 21 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycorine, which is an antitumor compound, has attracted attention for research recently. Lycorine is an isoquinoline alkaloid in Amaryllidaceae, which has antitumor, antibacterial, antiviral, diuretic and cardiovascular effects [1][2][3]. In recent years, the antitumor effect of lycorine has become a hot topic.…”
Section: Introductionmentioning
confidence: 99%
“…The continuously increasing interest in Amaryllidaceae alkaloids in the last years is based on important pharmaceutical properties. Galanthamine possesses anti-acetylcholinesterase activity, used for the treatment of Alzheimer’s disease, and is approved for use in the European Union and the United States [ 16 ]; lycorine possesses cytotoxicity and antitumor properties [ 17 ]; montanine possesses anxiolytic, antidepressant and anticonvulsive activities as well as immunomodulatory properties [ 18 ]; pancratistatin and narciclasine possess antitumor activity [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%